Impact of AMD processes on the water dams of the Iberian Pyrite Belt : overall hydrochemical characterization (Huelva, SW Spain) - Cerón, J. C. (2013)
In the Iberian Pyrite Belt (IPB), the process of acid mine drainage (AMD) is anthropogenic in origin. The impact of AMD pollution processes is characterised in 23 dams in the IPB. Based on the pH values, three groups are established: group 1 (pH<3), group 2 (pH 3–5) and group 3 (pH>5). Group 1 has the lowest pH values, with all of them lower than 3 and a minimum value of 1.9. The pH values are higher in the other groups, with lower values in group 2 (between 2.34 and 6.15) and higher in group 3 (between 4.36 and 7.58). Conductivity is higher in group 1 (varying between 1,005 and 12,280 μScm−1), while it takes intermediate values in group 2 (between 139 and 2,652 μScm−1), and group 3 is the lowest (between 80 and 750 μScm−1). Among the ions analysed, the concentration of sulphates stands out due to its magnitude, which is always greater than that of the other ions in the three groups. It is in group 1 that it reaches the highest values, with 6,200 mg/L, while it is lower in the others. Applying variable cluster analysis shows that in group 1, pH exercises control over the dissolution of most of the metals. It is also sulphates that control the value for conductivity. In group 2, precipitation is the main variable that controls the dissolution of ions, with the influence of pH being lower. In group 3, it is observed that in pH control metals, conductivity is controlled by sulphates.